2022
DOI: 10.3389/fonc.2022.1011091
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the optimal number of regional lymph nodes removed for resected N0 NSCLC patients: A population-based study

Abstract: BackgroundThe aim of our study was to explore the optimal number of regional lymph nodes removed (LNRs) in resected N0 non-small cell lung cancer (NSCLC) patients and identify potential risk factors.MethodsIncluded in this study were 55,024 N0 NSCLC patients between 2004 and 2015 based on the Surveillance, Epidemiology, and End Results database (SEER). All the patients were divided into No LNR group (57.8%), 1-3 LNRs group (8.1%) and ≥4 LNRs group (31.4%). Relevant clinical and patient parameters including ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…This underscores the importance of performing an adequate lymphadenectomy in improving the oncological outcomes of early-stage NSCLC patients (12). These findings align with other studies that have examined the number of harvested nodes at surgery and its association with survival (13). Patients who had a greater number of resected lymph nodes appeared to have better outcomes, and systematic lymphadenectomy with more than 10 harvested lymph nodes resulted in improved survival outcomes, particularly in a specific subgroup of patients with tumor diameter less than 20mm (14).…”
Section: Discussionsupporting
confidence: 83%
“…This underscores the importance of performing an adequate lymphadenectomy in improving the oncological outcomes of early-stage NSCLC patients (12). These findings align with other studies that have examined the number of harvested nodes at surgery and its association with survival (13). Patients who had a greater number of resected lymph nodes appeared to have better outcomes, and systematic lymphadenectomy with more than 10 harvested lymph nodes resulted in improved survival outcomes, particularly in a specific subgroup of patients with tumor diameter less than 20mm (14).…”
Section: Discussionsupporting
confidence: 83%
“…[18] Studies have demonstrated that a higher number of examined lymph nodes in NSCLC is associated with improved survival outcomes, likely due to more precise staging and the resultant tailored treatment strategies. [19][20][21][22][23][24][25][26] However, the application of these findings to SCLC is not straightforward due to the more aggressive nature and different treatment paradigms of SCLC.…”
Section: Discussionmentioning
confidence: 99%